1901 W.Va. Acts 197, An Act to Amend and Re-Enact Sections Two and Thirteen of Chapter Sixty-Two of the Code of One Thousand Eight Hundred and Ninety-Nine, ch. 89, § 1. - (:unkn) unknown (General Publisher, 1901)
No person shall shoot in the public road at any time, nor when shooting on the lands of another shall discharge any firearms on any lawn, pleasure ground or orchard or other ground which is directly appurtenant to or within gunshot of an occupied dwelling house. The penalty for violating this section shall be a fine of not less than five dollars nor more than twenty-five dollars, or imprisonment not more than twenty days, or both, at the discretion of the court, and pay the cost of the prosecution.
--
Keywords: DISCHARGE